(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
Citrus assamensis (Family: Rutaceae), commonly known as Satkara, is a pharmacologically diverse medicinal plant. In the present study, the leaf extracts of C. assamensis were subjected to evaluate in vitro anti-diabetic as well as in vivo anti-diarrheal, gastrointestinal motility and acute toxicity activity on Swiss albino mice by using standard protocol. Ethanol and chloroform extracts showed significant inhibitory potentials (**p<0.01) against in vitro α-amylase enzyme at the concentration of 80μg/mL. Significant (*p<0.05, **p<0.01, ***p<0.001) reduction in the number of wet feces and percentage inhibition of diarrheal activity over three hours was observed with all the test doses of the extract compared with the vehicle treated group. Both doses of methanol and ethanol extracts (*p<0.05) and chloroform extract at doses of 100 mg/kg significantly reduced the number of wet feces compared to the control. None of the extracts showed any significant in vivo acute toxicity effect on mice. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 111-120, 2018